2015
DOI: 10.1111/eva.12300
|View full text |Cite
|
Sign up to set email alerts
|

Using an integrative approach to investigate the evolution of behaviour

Abstract: Behaviour is a central focus of interest in biology because it has an impact on several aspects of an organism's life. Evolutionary biologists have realised the advantage of an integrative approach that jointly studies the molecular, cellular and physiological levels of an individual to link them with the organismal behavioural phenotype. First, this mechanistic information helps in understanding physiological and evolutionary constraints acting on the behavioural response to the environment and its evolution.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 145 publications
(249 reference statements)
0
14
0
Order By: Relevance
“…These receptors are expressed in a variety of tissues in fish, including the brain [Pimephales promelas (Giltrow et al 2011)], but their role in the central nervous system is less studied. Our results uncover a potential new association between this receptor and stress physiology, and suggest that the functional implication of their higher expression in more aggressive, more active, less social and less reactive fish (Di Poi et al 2014, 2016 should be further studied. In the glucocorticoid network, we found higher expression of the mc2r receptor in the interrenal glands of freshwater fish.…”
Section: Functional Implications Of the Differential Regulation Of Prnsmentioning
confidence: 69%
See 2 more Smart Citations
“…These receptors are expressed in a variety of tissues in fish, including the brain [Pimephales promelas (Giltrow et al 2011)], but their role in the central nervous system is less studied. Our results uncover a potential new association between this receptor and stress physiology, and suggest that the functional implication of their higher expression in more aggressive, more active, less social and less reactive fish (Di Poi et al 2014, 2016 should be further studied. In the glucocorticoid network, we found higher expression of the mc2r receptor in the interrenal glands of freshwater fish.…”
Section: Functional Implications Of the Differential Regulation Of Prnsmentioning
confidence: 69%
“…The lake is not connected to the ocean, and this population has been isolated from marine ancestors for approximately 10 000 years. Previous studies showed that common environment-reared fish originating from these htr1a 5HT populations differed in behaviours, stress reactivity, transcriptomic response to rearing temperature and cold tolerance (Barrett et al 2011;Di Poi et al 2014, 2016Morris et al 2014).…”
Section: Populations and Common Environmentmentioning
confidence: 98%
See 1 more Smart Citation
“…The research they describe reflects the strength and diversity of evolutionary biology today, regardless of gender. The articles in this special issue span the breadth of areas in evolutionary biology and touch upon many of the hottest topics, including sex chromosome evolution (Charlesworth ), sexual selection (Servedio ; Wellenreuther and Sánchez‐Guillén ), behavioural evolution (Aubin‐Horth ; Charmantier et al. ), evolution of cooperation (Aktipis ), diversification and speciation (Charmantier et al.…”
Section: Revising Perceptions Of Women In Evolutionary Biologymentioning
confidence: 99%
“…Gillespie () describes her now‐classic work in the Hawaiian archipelago on spider diversification, which spans a range of low levels of ‘nonadaptive radiation’ in some groups (without ecological diversification) to high levels of adaptive radiation (new species formation with ecological diversification). Aubin‐Horth () describes the exciting emergence of ecological genomics as a subfield, which has opened up the black box linking molecules and environmental cues to phenotypic and behavioural variation, focusing on her work on salmonid alternative reproductive tactics.…”
Section: Revising Perceptions Of Women In Evolutionary Biologymentioning
confidence: 99%